HIV epidemiology and responses among men who have sex with men and transgender individuals in China: a scoping review. Issue 1 (December 2016) - Tang, Songyuan; Tang, Weiming; Meyers, Kathrine; Chan, Polin; Chen, Zhongdan; Tucker, Joseph
Abstract Background Despite global efforts to control HIV among key populations, new infections among men who have sex with men (MSM) and transgender (TG) individuals are still increasing. The increasing HIV epidemic among MSM/TG in China indicates that more effective services are urgently needed. However, policymakers and program managers must have a clear understanding of MSM/TG sexual health in China to improve service delivery. To meet this need, we undertook a scoping review to summarize HIV epidemiology and responses among MSM and TG individuals in China. Methods We searched MEDLINE, EMBASE and the Cochrane Library for recent studies on MSM/TG HIV epidemiology and responses. We also included supplemental articles, grey literature, government reports, policy documents, and best practice guidelines. Results Overall, HIV prevalence among Chinese MSM was approximately 8 % in 2015 with a higher prevalence observed in Southwest China. TG are not captured in national HIV, STD, or other sexual health surveillance systems. There is limited data sharing between the public health authorities and community-based organizations (CBOs). Like other low and middle income countries, China is challenged by low rates of HIV testing, linkage, and retention. Several pilot interventions have been shown to be effective to increase HIV testing among MSM and TG individuals, but have not been widely scaled up. Data from two randomized controlled trials suggests that crowdsourcing contests can increase HIV testing, creating demand for services while engaging communities. Conclusion Improving HIV surveillance and expanding HIV interventions for Chinese MSM and TG individuals are essential. Further implementation research is needed to ensure high-quality HIV services for MSM and TG individuals in China.